(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the biological structure of the medicinal plant portulaca oleracea, its origin, its long-standing value as a medicinal plant, its distribution areas, and its composition of flavonoids, alkaloids, terpenoids, organic acids, vitamins, minerals, omega-3 fatty acids and their chemical properties. shown with structures. About the role of the substances contained in medicinal portulaca oleracea in the human body and what types of diseases they help in the treatment of various diseases, and the importance of modern medicine and folk medicine in the treatment of various diseases, that it is a promising medicinal plant, antioxidant, anti-inflammatory, antimicrobial, hypolipidemic, diabetes showing a number of pharmacological activities, including against and others, and the preparation of a food supplement from this plant compared to the synthetic drugs used by the members of our society in the prevention of negative effects on the human body and in the treatment of diseases covered with extensive information on its usefulness. Information is given on the fact that the production of food additives is convenient in every way: the raw materials are cheap, they are environmentally friendly, the production processes are not complicated, and they grow in almost all regions of our country, which means that the search for raw materials does not cause problems.